Haematological Parameters of Japanese Quails (Coturnix coturnix japonica) Subjected to High Stocking Density - S.O., Aro; J.O., Arogbodo; O.F., Ademola (International Journal of Scientific Research in Biological Sciences, 2021)
This study evaluated high stocking density and its effect on haematological parameters of 296 day-old apparently healthy Japanese quails for a period of eight weeks. They were divided into four stocking densities of 252.20 cm2/bird (11birds); 173.43 cm2/bird (16 birds), 132.10 cm2/bird (21birds), and 106.73 cm2/bird (26 birds) that represented Treatments I-IV respectively. The treatments were replicated four times adopting a completely randomized (CRD) design. Blood samples were drawn through their jugular veins into Ethylene di-amine tetra acetic acid (EDTA) and plain bottles for haematology and serum biochemistry respectively. Analyses of the blood samples were done using standard laboratory protocols. The haematological and serum biochemistry results differed significantly (p < 0.05) among the treatments. The haemogram revealed a corresponding (p < 0.05) rise in erythrocyte sedimentation rate (ESR), mean corpuscular volume (MCV) and mean corpuscular haemoglobin (MCH) as the stocking density increased while haemoglobin, red blood corpuscles (RBC), packed cell volume and mean corpuscular haemoglobin concentration (MCHC) decreased (p < 0.05) correspondingly The leuckogram showed a significant increase in the lymphocytes while heterophils decreased significantly relative to the stocking density. The minimum and maximum osmotic fragility for quails in this study was estabilished at 0.30 % and 0.10 % saline concentration respectively. Serum proteins, cholesterol, glucose, urea and alanine amino transferase were not affected by high stocking density but the treatment effects lowered the triglyceride component and concomitantly increased the high density lipoprotein components of the total cholesterol. Conclusively, most of the haematological parameters including the osmotic fragility of RBCs were negatively affected by high stocking density of 106.73 cm2/bird (TIV). Therefore, the stock densities of 173.43 cm2/bird (TII) and 132.10 cm2/bird (TIII) could be used for profitable quail production where there are constraints on land for this rapidly expanding backyard poultry venture.